The Influence of Sales Growth, Profitability, Liquidity and Firm Size Towards Financial Distress - Arief, Harefan; Saratian, Eko Tama Putra; Oktaviar, Chairiel; Marlapa, Eri; Soelton, Mochamad (PT FORMOSA CENDEKIA GLOBAL, 2024)
There are several models that can be used in analyzing a company's Financial Distress, the most widely used is the Altman model. The study aims to analyze and identify the influence of fundamental factors represented by ratios such as Sales Growth Analysis, ROA Ratio, Current Ratio, and Firm size on Financial Distress conditions. This research was conducted on financial statements of oil and gas mining sector. Data was collected using data panel with multiple linear regression technique analysis. Data was proceed using Eviews 12. The result show Sales growth, ROA, Current Ratio and TATO ratio have a partially significant effect on Financial Distress. Sales growth ROA, Current Ratio and TATO ratio together and a simultaneous have an effect on Financial Distress